ASSESSING THE ROLE OF SUSTAINABLE DEVELOPMENT IN MITIGATING THE ISSUE OF GLOBAL WARMING - Sahoo, Sushil Kumar; Das, Ashes Kumar; Samanta, Sourav; Goswami, Shankha Shubhra (Journal of process management and new technologies, 2023)
The relationship between Sustainable Development (SD) and Global Warming (GW) is a critical issue that has implications for the future of our planet. This research paper explores the ways in which SD can help address GW and the ways in which GW can impact SD. The paper argues that SD can help mitigate the negative impacts of Climate Change (CC) by promoting the use of renewable energy, reducing waste and pollution, and promoting sustainable land use practices. However, achieving SD in the context of GW requires a holistic approach that balances economic, social, and environmental concerns. Furthermore, the paper discusses the ways in which GW can impact SD by disrupting ecosystems, reducing the availability of natural resources, and increasing the risk of natural disasters. It also highlights the importance of adopting policies and practices that address the root causes of GW, while promoting SD practices that benefit all people and the planet. The research paper concludes that achieving SD and addressing GW are two interconnected issues that must be prioritized to ensure a healthy and prosperous future for all people and the planet. It calls for urgent action and collaboration among governments, businesses, and individuals to adopt SD practices and reduce Greenhouse Gas Emissions (GHGE).